Self-Management Components as Experienced by People with Parkinson's Disease and Their Carers: A Systematic Review and Synthesis of the Qualitative Literature. (15th December 2020) - Tuijt, Remco; Tan, Aylin; Armstrong, Megan; Pigott, Jennifer; Read, Joy; Davies, Nathan; Walters, Kate; Schrag, Anette
Abstract : Background . Self-management strategies are important in healthcare for people with Parkinson's to improve daily living. There is limited evidence on effectiveness in Parkinson's, and the active components of effective self-management strategies are uncertain. This review aims to identify and synthesise the qualitative evidence regarding the experiences of self-management components by people with Parkinson's and their carers. Methods . MEDLINE, PsycINFO, Embase, Web of Science, and CINAHL were searched from inception to July 8, 2020, for qualitative research concerning self-management for people with Parkinson's. Data were coded and thematically synthesised using NVivo. Findings . Of 9547 search results, six papers were included in the final thematic synthesis. The studies reviewed consisted of 147 participants: 104 were people with Parkinson's and 43 were carers. Seven main themes were derived concerning self-management of people with Parkinson's: (1) medication management, (2) physical exercise, (3) self-monitoring techniques, (4) psychological strategies, (5) maintaining independence, (6) encouraging social engagement, and (7) providing knowledge and information. These components should be incorporated as relevant strategies and techniques and should be specific as well as tailored to different stages of the disease. Discussion . Self-management programmes for people with Parkinson's should include the seven themes presented as part of this review and pay particular attention to presenting relevant information and skills as they relate to different stages of the disease. Tailoring information and social engagement were two components that required specific attention in order to engage people with Parkinson's effectively.